Arteriovenous fistulas of the Vein of Galen region in adults: Endovascular treatment. Issue 6 (December 2020) - Paúl, Laura; Casasco, Alfredo; Gil, Alberto; Aleu, Aitziber; Guimaraens, Leopoldo
Purpose: Arteriovenous fistulas of the Vein of Galen region in adults (Ad-VGAVF) are an uncommon entity with specific anatomic features. The aim of this article is to present our experience in the endovascular treatment of this pathology and to propose a therapeutic strategy based precisely on the angioarchitecture of these lesions. Materials and methods: During a 20-year period, 10 patients underwent endovascular treatment of Ad-VGAVF. They were nine men and one woman with a mean age of 50 years (23–66 years) treated with the same embolization strategy. Clinical presentation, angiographic characteristics, therapeutic strategy, and clinical outcomes were recorded. Results: All patients were treated exclusively by endovascular approach. Transarterial access was performed in eight patients and combined transvenous and transarterial access in two. Complete obliteration of the fistula was obtained in all patients. There were no intraprocedural complications. Post-embolization neurological symptoms occurred in 5 of 10 with complete resolution at six months in all of them. Conclusion: Arteriovenous fistulas of the Vein of Galen region in adults present uniform angioarchitecture despite their low prevalence. Based on this constant angioarchitecture and especially on the features of its venous drainage, judicious embolization strategy is feasible and effective. Ten cases treated entirely by endovascular approach with excellent clinical and angiographic outcomes show this treatment like a curative alternative for this entity of deep topography and severe prognosis.